Web-based map on knowledge and tools on implementation science for nutrition to support Scaling up Nutrition (SUN) countries - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Available online through a web-based data visualization tool called kumu. Information on its development, recommended uses, and other related resources are described in the A4NH briefs. Co-developed by A4NH researchers from the International Food Policy Research Institute, through the Knowledge for Implementation and Impact Initiative (KI3).